Constellar dialogue: the neobaroque in Haroldo de Campos - Andrade, Antonio (Revista de Letras, 2007)
This essay focuses on the tension between concretism and neobaroque in the Haroldo de Campos' oeuvre as a way of reconfiguration of the paradigms established by the concrete vanguard. The present work highlights Campos' important dialogue with representative Hispanic-American poets and critics of the neobaroque, as well as the simultaneous presence of the aesthetic notions of ideogram and constellation in the center of his poetical work.